2017
DOI: 10.1021/acs.est.7b04097
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Cr(VI) Generation from CrxFe1–x(OH)3 Solids upon Reaction with Manganese Oxide

Abstract: The reaction of manganese oxides with Cr(III)-bearing solids in soils and sediments can lead to the natural production of Cr(VI) in groundwater. Building on previous knowledge of MnO as an oxidant for Cr(III)-containing solids, this study systematically evaluated the rates and mechanisms of the oxidation of Cr(III) in iron oxides by δ-MnO. The Fe/Cr ratio (x = 0.055-0.23 in CrFe(OH)) and pH (5-9) greatly influenced the Cr(VI) production rates by controlling the solubility of Cr(III) in iron oxides. We establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 53 publications
(106 reference statements)
8
90
1
1
Order By: Relevance
“…Because CrO 4 2− is normally found under oxidizing conditions, Cr(OH) 3 dissolution is a potential pathway for the return of CrO 4 2− to the newly remediated groundwater if the redox conditions have not been altered, particularly in the presence of Mn(IV) oxides [61]. Studies of Cr(III) hydroxide redox behavior in soils [9][10][11]62] have shown that biogenic Mn(IV) oxides in soils can reverse the reductive transformation of chromate by oxidizing soluble Cr 3+ . The limiting factor in this process is the solubility of the Cr(III)-bearing phases (incorporation into ferrihydrite decreased oxidation by 37%), so the product produced in these reactions suggests that this method is unsuitable.…”
Section: Implications For Use In Permeable Reactive Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Because CrO 4 2− is normally found under oxidizing conditions, Cr(OH) 3 dissolution is a potential pathway for the return of CrO 4 2− to the newly remediated groundwater if the redox conditions have not been altered, particularly in the presence of Mn(IV) oxides [61]. Studies of Cr(III) hydroxide redox behavior in soils [9][10][11]62] have shown that biogenic Mn(IV) oxides in soils can reverse the reductive transformation of chromate by oxidizing soluble Cr 3+ . The limiting factor in this process is the solubility of the Cr(III)-bearing phases (incorporation into ferrihydrite decreased oxidation by 37%), so the product produced in these reactions suggests that this method is unsuitable.…”
Section: Implications For Use In Permeable Reactive Barriersmentioning
confidence: 99%
“…Several viable remediation methods exist that are capable of driving this transformation, including Fe 2+ and dithionite [5], zero-valent iron [6][7][8], and green rust, a layered Fe(II)-Fe(III) hydroxide mineral. However, several recent studies [9][10][11] have investigated the regeneration of chromate from Cr(III) and Cr(III)-bearing Fe(III) hydroxides in packed column experiments. These studies revealed that biogenic Mn(IV) oxides are the primary oxidant in these systems and that reductive transformation of chromate in soils may be reversible, depending on the Mn content and redox conditions of the soils as well as the solubility of the Cr(III)-bearing phase.…”
Section: Introductionmentioning
confidence: 99%
“…While laboratory studies have investigated how differences in mineral solubility control Cr(VI) generation without contact with reactive Mn oxides [19], to our knowledge there have been no experimental studies to investigate the relative impact of diffusion distance and solubility. This is likely to be due to experimental difficulties associated with designing and measuring nano-to microscale systems.…”
Section: Hydrologic Constraints On Cr(vi) Concentrationsmentioning
confidence: 99%
“…Redox transformations between the two forms occur in response to changing redox conditions; these transformations are often mediated by other metal biogeochemical cycles. Cr(III) oxidation to Cr(VI) is primarily mediated by biogenic Mn(IV) oxides [5][6][7], and the synthetic counterpart δ-MnO 2 has been used to assess the lability of synthetic Cr(III)-bearing phases [8,9]. However, no published study to date has used this method to assess the stability of Cr(III) carrier phases generated by a lab-scale in situ chemical reduction study.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, pure sulfate GR and sulfate GR with isomorphic substitution of Al, Mg, and Zn were synthesized and reacted with Cr(VI). The lability of Cr(III) in the reaction products was then determined by measuring the release of Cr(VI) after treatment with synthetic δ-MnO 2 , the synthetic counterpart of biogenic Mn oxide which has been used to assess Cr lability in previous studies [7][8][9]. The structure and Cr speciation of these products were also determined using transmission electron microscopy (TEM), X-ray absorption spectroscopy (XAS), X-ray diffraction (XRD) and pair distribution function (PDF) analysis.…”
Section: Introductionmentioning
confidence: 99%